Speaking of Profit Bao Shichen and Reform in Nineteenth-Century China. - Rowe, William T. (Harvard University Studies in East Asian Law Ser., 2018)
"The Qing Empire faced a crisis in the nineteenth century of corruption, population pressure, food shortages, ecological and infrastructural decay, rebellion, and a foreign threat from the West. This study uses the literati reformer Bao Shichen as a prism to understand contemporary perceptions of and proposed solutions to this crisis"--Provided by publisher.